Effect of Different K/Ca Ratios on Yield and Quality of Greenhouse Roses - Boztok, Senol; Cokuysal, Burcin (Asian Journal of Chemistry, 2010)
The rooted cuttings of rose (Rosa hybrida L.) were grown under greenhouse conditions in 25% turf + 75% soil. The experiment was set up in November 1999 and was completed after last harvest in April 2001. The purpose of this research was to determine the effect of different K/Ca ratios on some quality parameters, leaf nutrient status and yield of rose. The applied ratios were 1/1, 1/3 and 3/1. Results of analysis have shown that the higher K/Ca ratio increased the uptake of K and reduced the uptake of Ca. And also, the highest length of stem, number of extra class flower, number of first class flower, total yield and yield for November to March was found the highest K/Ca ratio (3/1) application.